KNOWLEDGE OF CARDIOVASCULAR RISK FACTORS IN UNIVERSITY STUDENTS - Nader, Jorge Elias Daher; Mazzini, Manuel Balladares; Navarro, Marlene Isabel Hernandez; Salazar, Manuel Balladares; Vélez, María Sánchez; Alvarez, Alexandra Alvarado (International Journal of Research -GRANTHAALAYAH, 2020)
The incidence of cardiovascular diseases has reached alarming figures in many regions of the world, including Ecuador. One of the objectives of medical universities is to train professionals capable of transforming the health status of the population from primary health care, in order to achieve the prevention of modifiable cardiovascular risk factors through changes in lifestyle. Objective: To determine the level of knowledge about cardiovascular risk factors in university students of the Faculty of Medical Sciences of the University of Guayaquil of Ecuador. Methods: This is a quantitative, observational, descriptive and cross-sectional study conducted at the Faculty of Medical Sciences of the University of Guayaquil. The population consisted of a total of 183 students and the sample was made up of 125 students. Results: The students of the Obstetrics and Bachelor of Nursing degrees have less knowledge about cardiovascular risk factors than the students of the Medicine, Medical students (86%) and nursing (71%) consider cardiovascular diseases as the main causes of death, while those of obstetrics barely 40%, prioritizing almost to traffic accidents as one of the first causes. Conclusions: The needs to actively incorporate health promotion from university classrooms to incorporate in the mental structure of students and teachers the imperative need to generate individual changes and then generate health in society were identified.